226k views
2 votes
Please help asap.I don't understand ​

Please help asap.I don't understand ​-example-1

1 Answer

1 vote

Answer:

see explanation

Explanation:

Given the zero x = a of f(x) then f(a) = 0

(5)

f(9) =9³ - 8(9)² - 2(9) - 63 = 729 - 648 - 18 - 63 = 0

Hence x = 9 is a zero of the polynomial

(6)

2
(-3)^(4) - 3(- 3)³ - 36(- 3)² - 37(- 3) - 26 = 162 + 81 - 324 + 111 - 26 = 4 ≠ 0

Hence x = - 3 is not a zero of the polynomial

User Sahil Kalra
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.